2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2018
DOI: 10.1109/vr.2018.8446059
|View full text |Cite
|
Sign up to set email alerts
|

Text Entry in Immersive Head-Mounted Display-Based Virtual Reality Using Standard Keyboards

Abstract: We study the performance and user experience of two popular mainstream text entry devices, desktop keyboards and touchscreen keyboards, for use in Virtual Reality (VR) applications. We discuss the limitations arising from limited visual feedback, and examine the efficiency of different strategies of use. We analyze a total of 24 hours of typing data in VR from 24 participants and find that novice users are able to retain about 60% of their typing speed on a desktop keyboard and about 40-45% of their typing spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 37 publications
0
95
0
3
Order By: Relevance
“…They reported mean text-entry rates of 24.3-28.1 WPM and mean total ER of 20%-28%. Grubert et al (2018) investigated the performance of two desktop keyboards and two touchscreen keyboards for VR text entry. The mean text-entry rates achieved with the two desktop keyboard interfaces were 26.3 WPM and 25.5 WPM (and character error rates were 2.1% and 2.4%), separately.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported mean text-entry rates of 24.3-28.1 WPM and mean total ER of 20%-28%. Grubert et al (2018) investigated the performance of two desktop keyboards and two touchscreen keyboards for VR text entry. The mean text-entry rates achieved with the two desktop keyboard interfaces were 26.3 WPM and 25.5 WPM (and character error rates were 2.1% and 2.4%), separately.…”
Section: Related Workmentioning
confidence: 99%
“…Since the early days of virtual reality (VR), various text-input techniques have been developed and studied to achieve seamless and user-friendly typing in virtual environments. Prior works have investigated many interaction methods for typing in VR, such as wearable gloves, specialised controllers, head and gaze direction, pen and tablet keyboards, virtual keyboards, touchscreen keyboards, augmented virtuality keyboards, speechto-text, and hand and finger gestures (Lepouras, 2018;Lee and Kim, 2017;Grubert et al, 2018;Yu et al, 2017;McGill et al, 2015;Bowman, Rhoton, and Pinho, 2002). and attempts to build on these widely used techniques are ongoing (Lee and Kim, 2017;Oberhauser and Lecon, 2017;George et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…VR is not compelled to follow the physical rules of our real world. Recent research has indicated that the location of the virtual and physical keyboard can differ without affecting text entry performance [31]. However, apart from changing the location of the virtual keyboard, further modifications of its visual representation or functionality has not been thoroughly investigated within VR.…”
Section: Introductionmentioning
confidence: 99%
“…Grubert et al [7] investigated the performance of physical and touch keyboards and physical/virtual co-location for VR text entry.…”
Section: Keyboards For Vrmentioning
confidence: 99%
“…However, while direct transplantation of standard keyboards to VR is viable, there are critical design parameters that should be investigated since it is plausible they affect performance. In a companion paper [7] we investigate the performance of physical and touch keyboards and physical/virtual co-location for VR text entry.…”
Section: Introductionmentioning
confidence: 99%